Minnesota Multiphasic Personality Inventory‐Adolescent‐Restructured Form (MMPI‐A‐RF) characteristics of ADHD in a Korean psychiatric sample. Issue 5 (26th October 2021) - Chakranarayan, Cheryl; Weed, Nathan C.; Han, Kyunghee; Skeel, Reid L.; Moon, Kyungjoo; Kim, Ji‐Hae
Abstract: Global rates of attention‐deficit/hyperactivity disorder (ADHD) have risen. In Korea, ADHD is associated with functional impairments and comorbidity with other psychological disorders. This study examined the correlates of ADHD in a psychiatric sample of Korean adolescents on the Minnesota Multiphasic Personality Inventory‐Adolescent‐Restructured Form (MMPI‐A‐RF). In a clinical sample of 247 adolescents, MMPI‐A‐RF scores from 46 patients diagnosed with ADHD were compared to the remainder of the clinical sample and to the Korean MMPI‐A‐RF norms. Results demonstrated significantly different scores for the ADHD group on scales indicating externalizing concerns and behavior dysfunction compared with the clinical group with other disorders and to a normative sample. Notable differences were also observed between clinical groups on scales reflecting interpersonal functioning. Relative risk ratio analyses demonstrated that an MMPI‐A‐RF T‐score of 55 was generally most effective for predicting risk for an ADHD diagnosis in the clinical sample.